INDIAN CIVIL LAWS GOVERNING RELIGIOUS CONVERSION - Manickam, Thomas (2003)
In the Constitution of India, adopted in the Constituent Assembly as the Law of the Land on November 26, 1949, the fourth fundamental right of all the citizens of India is titled as "Right to Freedom of Religion." This fundamental right is formulated in Article 25 of the Constitution as follows: Art. 25. (1) Subject to public order, morality and health and to the provisions of this Part, all persons are equally entitled to freedom of conscience and the right freely to profess, practice, and propagate religion. (2) Nothing in this article affect the operation of any existing law: (a) regulating or restricting any economic, financial, political or other secular activity which may be associated with religious practice; (b) providing for social welfare and reform or the throwing open of Hindu religious institutions of a public character to all classes and sections of Hindus.
Keywords: Conversion; Civil Laws; Freedom